Evaluación técnico financiera del uso de una emulsión inversa de crudo pesado, en la caldera, para el proceso de inyección cíclica de vapor del Campo Girasol (2017)
The technical financial evaluation of the use of a reverse emulsion of heavy crude was carried out in a boiler, with the objective of analyzing the behavior of the combustion efficiency when using a fuel different from the conventional oil of Campo Girasol. For this, a reverse emulsion was prepared with 20% water and 80% Girasol crude using a nonionic emulsifier. The emulsion was analyzed for the distribution parameters and droplet size, as well as its stability, verifying that it did not present any breaking off.